Differentiated SH-SY5Y neuroblastoma cells as a model for evaluation of nerve agent-associated neurotoxicity - Pulkrabkova, Lenka; Muckova, Lubica; Hrabinova, Martina; Sorf, Ales; Kobrlova, Tereza; Jost, Petr; Bezdekova, Dagmar; Korabecny, Jan; Jun, Daniel; Soukup, Ondrej (Archives of toxicology, 2023)
Organophosphorus compounds (OPs) involving life-threatening nerve agents (NA) have been known for several decades. Despite a clear mechanism of their lethality caused by the irreversible inhibition of acetylcholinesterase (AChE) and manifested via overstimulation of peripheral nicotinic and muscarinic acetylcholine (ACh) receptors, the mechanism for central neurotoxicity responsible for acute or delayed symptoms of the poisoning has not been thoroughly uncovered. One of the reasons is the lack of a suitable model. In our study, we have chosen the SH-SY5Y model in both the differentiated and undifferentiated state to study the effects of NAs (GB, VX and A234). The activity of expressed AChE in cell lysate assessed by Ellman's method showed 7.3-times higher activity in differentiated SH-SY5Y cells in contrast to undifferentiated cells, and with no involvement of BuChE as proved by ethopropazine (20 μM). The activity of AChE was found to be, in comparison to untreated cells, 16-, 9.3-, and 1.9-times lower upon A234, VX, and GB (100 μM) administration respectively. The cytotoxic effect of given OPs expressed as the IC50 values for differentiated and undifferentiated SH-SY5Y, respectively, was found 12 mM and 5.7 mM (A234), 4.8 mM and 1.1 mM (VX) and 2.6 mM and 3.8 mM (GB). In summary, although our results confirm higher AChE expression in the differentiated SH-SY5Y cell model, the such higher expression does not lead to a more pronounced NA cytotoxic effect. On the contrary, higher expression of AChE may attenuate NA-induced cytotoxicity by scavenging the NA. Such finding highlights a protective role for cholinesterases by scavenging Novichoks (A-agents). Second, we confirmed the mechanism of cytotoxicity of NAs, including A-agents, can be ascribed rather to the non-specific effects of OPs than to AChE-mediated effects.
Keywords: Neuroblastoma; nervová bojová látka; Acetylcholinesterase; lidé; neuroblastom; Nerve Agents; Antineoplastic Agents; neurotoxické syndromy; protinádorové látky; Cell Line, Tumor; acetylcholinesterasa; Neurotoxicity Syndromes; nádorové buněčné linie; Humans